Digital Leadership Styles and Their Impact on Remote Team Collaboration Effectiveness in Global Virtual Firms - Syaefullah Syaefullah; Chitra Indah Sari; Abdal Ahmed (International Forum of Researchers and Lecturers, 2024)
The evolution of global virtual firms in the post-pandemic era has transformed the dynamics of leadership, collaboration, and team performance. This study investigates the influence of digital leadership styles-particularly transformational, transactional, and adaptive-on the effectiveness of collaboration among remote teams operating in multinational virtual environments. Using a mixed-methods approach that integrates quantitative surveys and qualitative interviews, data were collected from managers and team leaders of multinational corporations who lead geographically dispersed teams. Quantitative findings reveal that adaptive and transformational digital leadership styles significantly enhance communication, coordination, trust, and motivation within remote teams, while transactional leadership proves less effective in sustaining engagement across time zones and cultural boundaries. Qualitative insights highlight that flexibility, empathy, and digital literacy are central to building trust and cohesion in diverse virtual settings. Moreover, the use of advanced collaboration tools such as Slack, Microsoft Teams, and Zoom amplifies leadership effectiveness when aligned with inclusive communication practices. The study underscores that successful digital leadership depends on balancing human-centered empathy with technological competence to foster team cohesion and innovation. Managerial implications emphasize the need to develop leaders’ digital competencies and cross-cultural communication skills, along with fostering adaptive strategies to sustain engagement in virtual work environments. Future research should explore the longitudinal effects of digital leadership development programs across industries to assess their sustained impact on productivity, innovation, and organizational resilience in digital ecosystems.